Analisis Usability Pada Sistem Informasi LAPORBUP Menggunakan Performance Measurement, Retrospective Think Aloud dan User Experience Questionnaire - Mohamad Ariansidi; I Made Candiasa; I Made Gede Sunarya (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
Since 5 years of its use until now there has never been an evaluation at LAPORBUP and it is not yet known how high the level of user satisfaction is in using LAPORBUP. In addition, several problems were found in LAPORBUP which were felt by users related to the interface and system functionality. These problems indicate that LAPORBUP is still not in accordance with the needs, it is necessary to carry out an evaluation analysis of the overall usability of the system by measuring the effectiveness and efficiency as well as the level of user satisfaction. The LAPORBUP evaluation involved 54 respondents obtained from OPD representatives and active users of LAPORBUP. Processing of this evaluation data is carried out using the Performance Measurement technique to measure system effectiveness and efficiency, as well as Retrospective Think Aloud and User Experience Questionnaire to measure aspects of user satisfaction. The results of the Performance Measurement evaluation show that the LAPORBUP application has not been effective because several problems were found when the respondents worked on the task scenarios. Furthermore, UEQ data analysis was carried out using the UEQ Data Analysis Tool by comparing the value of each aspect with the available product data set. Based on the analysis conducted, the attractiveness aspect is included in the good category with a value of 1.72. The clarity aspect is included in the category above the average with a value of 1.48. The efficiency aspect is included in the category above the average with a value of 1.18. The aspect of accuracy is included in the good category with a value of 1.55. The stimulation aspect is included in the very good category with a value of 2.13. The novelty aspect is included in the Very Good category with a value of 1.64. The recommendations generated from Retrospective Think Aloud consist of 7 recommendations on the complaints page, 14 recommendations on the management page, 10 recommendations on the regent's page, and 9 recommendations on the OPD page. The results of the analysis show that improvements can be made to aspects of clarity and efficiency so as to improve the quality of LAPORBUP services